Pengaruh Substitusi Abu Bonggol Jagung sebagai Pozzolan pada Semen Portland Komposit terhadap Kuat Tekan Mortar - Alif Nur Laili Rachmah; Binti Ruliana; Sabrianah Badaruddin; Ratih C F Ratumanan; Ronald Darlly Hukubun (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The effect of additive corn cob ash (CA) on Portland Composite Cement (PCC) on the compressive strength of the mortar is influenced by pozzolan. The material that makes up pozzolan is silica. Corn cobs are agricultural waste that contains silica and every year continue to increase, so corn cob waste is as an additional material to Portland Composite Cement (PCC). This study was conducted to determine the compressive strength value of mortar using additive corn cob ash (CA) and corn cob ash that has been washed with HCl 2N (CA*) and the feasibility of these additives as a PCC-type cement mixture. The weight percentages of additives used were 5%, 10%, and 15%, and the duration of the mortar compressive strength test was 3, 7, and 28 days. The experimental results showed that the compressive strength (σm) was highest at the addition of 5% additives, the effect of additives on compressive strength resulted in σm research > standard σm (SNI). The results of the activation index analysis obtained additive corn cob ash of 76% and corn cob ash+HCl 2N of 76.71%, the value is above the minimum limit according to ASTM C.618-99 which is 75%.